Integrating Islamic-Based Behavioral Activation with Buya Hamka's Tazkiyatun Nafs to Reduce Social Media-Induced Anxiety among University Students - Juliawati, Dosi; Yandri, Hengki; Kholidin, Farid Imam; Rasmita, Rasmita; Daflaini, Daflaini; Fidya, Yatti (citeus, 2025)
The pervasive use of social media has led to a growing concern regarding social media-induced anxiety among university students. This study aims to integrate Islamic-based Behavioral Activation with the concept of Tazkiyatun Nafs, defined as the purification of the soul or self-purification, as proposed by Buya Hamka, to reduce this anxiety among university students. The method employed is a Single-Subject Experimental Design involving three participants from IAIN Kerinci, all of whom exhibited the highest scores of social media anxiety. Data were collected using the Social Media Anxiety Scale (SMAS) and analyzed through visual data analysis. The results indicate that all three respondents showed a significant decrease in social media anxiety levels from the beginning to the end of the observation period. Specifically, visual analysis revealed a substantial reduction in SMAS scores, with participants' anxiety levels consistently dropping from high initial scores to significantly lower post-intervention scores. The intervention phase appeared to have a substantial positive impact, and the reduction in anxiety continued into the follow-up phase, albeit at varying levels. These findings suggest that the Islamic-based Behavioral Activation intervention, grounded in the Tazkiyatun Nafs concept, is effective in alleviating anxiety caused by social media use among students. The significant decrease in anxiety scores during both the intervention and follow-up phases confirms that the observed changes are not merely the result of natural fluctuations but rather the outcome of the implemented intervention. This research contributes important insights into the development of psychological intervention strategies based on Islamic values to address anxiety issues in the digital age, offering a valuable approach for practitioners and a foundation for future research on culturally sensitive mental health interventions.